The Value of a Gardening Service for the Frail Elderly and People With a Disability Living in the Community. (November 2016) - Same, Anne; Lee, Elinda Ai Lim; McNamara, Beverley; Rosenwax, Lorna
Little is known about the significance of gardening services for frail elderly people. This study explored the value of a gardening service for frail older people and people with a disability living in the community. Using qualitative and quantitative data collected from pre-gardening ( n = 38) and post-gardening service delivery interviews ( n = 35) and the Housing Enabler, the value of a gardening service was examined. Findings suggest that the service had a positive impact on the independence and emotional well-being of frail aged people and younger people with a functional disability, with little impact on physical health. Results indicate that gardening services should be fundamental to planning for these populations to remain or return to living in the community.